ALAT PEWARNA BATIK ROL GANDA (PEDER) - TAUFIQ HIDAYAT (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
One of the commodities of the creative industry in Indonesia, which until now is still superior, is the batik industry, both batik screen printing batik, stamp and printing. The stages of the production process of stamp batik are the process of tasting, coloring, drying and drying / drying. Problems that arise during the production process in batik UKM Pandanwangi is a coloring process that takes longer and is wasteful of the dye. The existence of a dye or dye tool is needed, a tool that is able to provide a solution to this problem is a peder. The purpose of implementing the partnership program for the community (PKM) is to help provide solutions specifically the problem of the production process. The method developed is a survey of UKM, designing tools, carrying out discussions with partners in relation to the results of tool design, tool manufacturing processes, component performance testing, work testing of tools and production processes. The results of the program are a peder with specifications: size of 157 cm x 149 cm x 144 cm, source of 0.5 Hp electric motor power, transmission (V-belt, pulleys, chains and gears), dye tanks, pressing (2 rollers and fasteners). The speed of the production process for the program results is 15 m per minute. The conclusion of the implementation of the PKM program is that SME partners are able to carry out the coloring / dyeing production process on average ± 2000 m every day.